Dukungan Organisasional Dan Kontrak Kerja Terhadap Kinerja Yang Dimediasi Oleh Employee Involvement Pada Karyawan Pt Xyz Indonesia - Cahyani, Prihantika Septi; Yuni Siswanti,; Purbudi Wahyuni, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine the effect of organizational support and employment contracts on employee performance, with employee involvement as a mediating variable, focusing on Generation Z contract employees at PT XYZ Indonesia. The research adopts the Social Exchange Theory (SET) framework, which emphasizes reciprocal relationships between employees and organizations. A quantitative approach was employed using purposive sampling, involving 104 respondents. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that organizational support has a positive but insignificant effect on employee performance, while employment contracts have a negative yet significant impact. Both organizational support and employment contracts significantly affect employee involvement. Moreover, employee involvement positively influences employee performance and partially mediates the relationship between employment contracts and performance. However, no mediating effect was found between organizational support and performance through employee involvement. This research highlights the importance of involving employees particularly Generation Z—in organizational processes to enhance performance outcomes. It also underscores that contract clarity and perceived organizational support must be managed carefully to foster engagement and productivity. The findings provide valuable insights for human resource practices, especially in managing young, contract-based workforces in creative industries.